Review of Paediatrics In-Patient at Nepal Medical College and Teaching Hospital - Upadhyay, S; Sharma, A; Rijal, P; Shrestha, S (Journal of Nepal Paediatric Society, 2011)
Introduction: This retrospective study was undertaken to analyze the disease pattern in the Pediatric ward in a Medical College. After analyzing the data, our study would emphasize on the prevention and the management modality of the most prevalent diseases in the community. Methodology: This study was carried out retrospectively for one year from January 2008 - December 2008 on the basis of age and sex and the frequency of disease according to the system involved. Results: A total number of 453 patients were admitted during the study period. There were 267(59%) male and 186(41%) female children. Less than five years age group accounted for 180(39.7%) excluding the neonate. In the study period, respiratory tract infections were the commonest cause of admission in all age group 198(43.7%), gastrointestinal including diarrhoeal diseases were 112(24.7%), enteric fever comprised of 22(5%), and other disease comprised of about 143(31.5%) of the total admissions. CNS diseases comprised of 43(9%) of which 7(16%) were meningitis and meningoencephalitis, 26(60%) of the total CNS cases were due to febrile convulsion. Respiratory diseases were found to be the major cause of morbidity in children. Conclusion: Children under five years age being the most common age group amongst all, with infection being the most predominant cause of Pediatric morbidity, the WHO/UNICEF algorithm for Integrated Management of Childhood Illness (IMCI) is specifically suited for the developing country like ours. Key words: Paediatric Inpatient; Morbidity; IMCI DOI: 10.3126/jnps.v31i1.3262 J Nep Paedtr Soc 2010;31(1):25-29